Tradisi Sukan Warna sebagai Media Dakwah Pendidikan Karakter di Pondok Pesantren As Saqofah Pombing Thailand - Muhammad Ridwan; M. Zuhrul Ikfa; M. Navidhiyaulhaq; Roykhan Hidayat; A. Kasyifan Sidqi; Faisal Faisal; Lina Tri Maulida; Isna Rosita Rahmah (Pusat Riset dan Inovasi Nasional, 2024)
This article reviews the role of the Color Sports Tradition in shaping the character of Fair Play at the As Saqofah Pombing Islamic Boarding School, Thailand. The main focus of the article is to explain how to use Color Sports as a tool to form the principles of sportsmanship, integrity and respect for others in sports competitions. The research method applied is a qualitative approach through in-depth interviews with coaches, students, and boarding school management staff. The results of the study show that the Color Sports Tradition has succeeded in becoming an efficient means of developing the character of students at the As Saqofah Pombing Islamic Boarding School. This tradition provides learning that the purpose of competition is not only limited to winning, but also emphasizes the importance of ethical and moral principles in competing. The principles of Fair Play apply to every aspect of the Sports of Color Tradition, resulting in a fair and mutually supportive competitive environment. Overall, the Color Sports Tradition at the As Saqofah Pombing Islamic Boarding School has proven to be a successful character building medium in teaching the principles of Fair Play to students. This approach has the potential to be adopted in other educational contexts, as well as to contribute to shaping young people who are not only good at sports, but also have sportsmanship, integrity, and respect for social values in various life situations.